Adjusting Household Structure: School Enrollment Impacts of Child Fostering in Burkina Faso - Richard Akresh (Yale University, Economic Growth Center, 2004)
Researchers claim that children growing up away from their biological parents may be at a disadvantage and have lower human capital investment. This paper measures the impact of child fostering on school enrollment and uses household and child fixed effects regressions to address the endogeneity of fostering. Data collection by the author involved tracking and interviewing the sending and receiving household participating in each fostering exchange, allowing a comparison of foster children with their non-fostered biological siblings. Foster children are equally likely as their host siblings to be enrolled after fostering and are 3.6 percent more likely to be enrolled than their biological siblings. Relative to children from non-fostering households, host siblings, biological siblings, and foster children all experience increased enrollment after the fostering exchange, indicating fostering may help insulate poor households from adverse shocks. This Pareto improvement in schooling translates into a long-run improvement in educational and occupational attainment.
Keywords: J12; I20; O15; D10; 330; Human capital investment; Child fostering; Household structure; Bildungsinvestition; Bildungsverhalten; Privater Haushalt; Kinderbetreuung; Burkina Faso